Integrating Corporate Social Responsibility and Pay What You Want for Sustainable Street Vendors in Surabaya - Hartono Hartono; Rahayu Rahayu (Research Synergy Foundation, 2026)
Street food vendors (Pedagang Kaki Lima/PKL) are an essential part of Indonesia’s informal economy, contributing significantly to employment while facing vulnerability and limited institutional support. This study aims to analyze how the integration of Corporate Social Responsibility (CSR) with the Pay What You Want (PWYW) pricing model can strengthen the economic and social sustainability of PKL in Surabaya. Using a qualitative case study approach, data were collected from 25 participants, including vendors, consumers, donor communities, individual donors, and government representatives, through focus group discussions, in-depth interviews, participatory observations, and document reviews, then analyzed thematically with NVivo. The findings reveal that PWYW increases consumer engagement and builds trust-based relationships, while CSR provides crucial support through training, capital assistance, and community education. Nevertheless, challenges remain in terms of income uncertainty and insufficient regulatory frameworks. The study highlights that multi-stakeholder collaboration among CSR actors, government, donors, and PKL is essential for sustaining the model. Theoretically, this research introduces the integration of CSR and PWYW as a hybrid social innovation in the informal economy, while practically, it offers strategic insights to strengthen microenterprise resilience and contribute to inclusive economic development